Students’ perception towards the time suitability for Indonesian language course - Ahmad Jum'a Khatib Nur Ali; Mohammad Siddiq (Mitra Palupi, 2022)
Background: Learning Indonesian Language in Higher Education level has a different focus from other levels. Learning Indonesian in tertiary institution does not only study the rules of the Indonesian language, but also implements them in scientific writing with an orientation to the use of technology. Indonesian language course also exists in foreign language study programs. One of the learning weight indicators is the time suitability as a key factor in the success of learning. Purpose: This study aims to find out the students’ perception of satisfaction level of English Literature study program, towards the time suitability for tasks in Indonesian Language course. Design and methods: This study uses a descriptive quantitative approach. The research method is a survey with the data collection instrument, the questionnaires. The research subjects are students who take the Indonesian language course at the English Literature Study Program, Universitas Gunadarma. The research sample is 148 respondents. Data collection is conducted in the even semester of the 2021/2022 academic year. The perception of the satisfaction level towards the time suitability for the Indonesian language course is conducted through 4 (four) indicators, namely; (1) study time, (2) structured task time, (3) independent task time, (4) exam time. Results: The results showed that there is a positive response to time suitability in Indonesian language course. As much as 73.64% of the sample respondents stated that it is very sufficient for learning time suitability, 74.32% is very sufficient for structured task time, 70.94% is very sufficient for time independent tasks and 70 .27% is very sufficient for exam time. Students’ perceptions of the time suitability for learning Indonesian course are positive with an average suitability of 72.29%, which is very sufficient